Broker decision verification system using MR cloud tree - Koneru, Anupriya; M, Sreelatha (International Journal of Engineering and Technology, 2026)
In the present industry, there is a gap between the requirements of the Cloud Service Requester and the services offered by Cloud Service Providers. To bridge this gap, Cloud Service Brokers extended their service towards the selection of Cloud Service Provider for Cloud Service Requester. In this process, the Broker may deceit and selects a bribery Provider that completely affects the Requesters business. This assumption shows the necessity of checking the correctness of the Cloud Service Broker. This paper focuses on proposing a Broker Decision Verification System which depends on MRcloud Tree. It works on multidimensional data to provide the cloud service requester with a facility to check the correctness of the Cloud Service Broker and also offers only a single provider to the Requester which could be done by Reputation Factor Value of the Provider. The performance of Broker Decision Verification System is compared with MBcloud Tree.